A novel multi-flaw MoS2 nanosheet piezocatalyst with superhigh degradation efficiency for ciprofloxacin. Issue 12 (30th October 2018) - Ma, Wei; Yao, Binghua; Zhang, Wen; He, Yangqing; Yu, Yan; Niu, Jinfen; Wang, Cheng
Abstract : A novel MoS2 piezoelectric nanocatalyst with multiple flaws exhibited ultrafast degradation of the antibiotic ciprofloxacin. Abstract : Multi-flaw MoS2 nanosheets were synthesized by a hydrothermal method by controlling the molar ratio of Mo and S. The physical and chemical properties and structures of the samples were characterized by SEM, TEM, N2 adsorption/desorption isotherms, XRD, Raman spectroscopy, and XPS. The construction of flaws with abundant exposed edges in the ultrathin MoS2 nanosheets played an important role in improving the piezocatalytic performance for the degradation of antibiotic ciprofloxacin (CIP) by forming the active sites. Compared with flaw-free MoS2, multi-flaw MoS2 nanosheets had a high number of atomic layers (abundant odd numbers of atomic layers) and exhibited excellent adsorption-piezocatalytic ability, decomposing 99% of CIP in 30 s under ultrasonic irradiation. Furthermore, the total organic carbon (TOC) analysis indicated that 56% of CIP was completely mineralized after 5 min of ultrasonic irradiation. The eradication mechanism of CIP followed pseudo-second-order kinetics with a maximum degradation rate constant of 1.29 L mg −1 s −1 . The superior piezocatalytic performance of multi-flaw MoS2 nanosheets was mainly attributed to the highly efficient separation of electron–hole pairs caused by the strain-induced piezoelectric field (an internal electric field). Active species trapping and terephthalic acid (TA) fluorescence experiments demonstrated that the hydroxyl radicals (˙OH) were the major reactive oxygen species that degraded CIP. In addition, UPLC-MS analysis was used for monitoring the intermediates in CIP decomposition. The complete opening of the piperazine and quinolinic rings and the formation of simpler aliphatic compounds were observed. A possible degradation pathway was proposed based on the UPLC-MS data. The ultrafast degradation efficiency of multi-flaw MoS2 nanosheets could be used for practical environmental remediation applications.